Adverbial clauses of time in spoken Lithuanian - Jasionytė-Mikučionienė, Erika; Bacevičiūtė-Kostiugovė, Janina (Lietuvių kalba, 2025)
The paper examines adverbial clauses of time in spoken Lithuanian. The data have been collected from The Corpus of Contemporary Lithuanian Language, namely its sub-corpus of spoken language. The aim of the study is to describe the structure of adverbial clauses, focusing on the semantic relationship between the main and dependent adverbial clause, the position of the dependent (or subordinate) clause in relation to the main clause, and subordinators introducing adverbial clauses as well as their functions. The results of the study show that in spoken language, adverbial clauses are most often connected by the subordinators kai ‘when’, kaip ‘how’, kol ‘while’, and kada ‘when’, performing also other than circumstantial functions. In spoken data, there are cases where the subordinator occupies not the initial, but the medial position, i.e., it is interposed between the subject (or the object) and the predicate. The latter fact is determined by the characteristics of spoken discourse: the subject or the object of the sentence is brought to the foreground; they are expressed by personal pronouns and their referents are the participants in the conversation, i. e., the speaker and the hearer. The position of the dependent (i. e. adverbial) clause depends on the semantic relation between the clauses of a complex sentence: for example, adverbial clauses denoting premature actions occur in the preposition, though in spoken language, as in written language, the postposition of the adverbial clause dominates. The correlation of the main predicate with the grammatical categories of time and aspect is also emphasized.
Keywords: adverbial time clauses; spoken language; semantic relationship; main clause; subordinate clause; adverbial conjunctions